Experimental investigation of an indoor air purification system using an innovative photocatalytic mop - Riffat, James (2023)
This thesis presents a comprehensive investigation of "MopFan," a photocatalytic air purification system, with the overarching goal of improving indoor air quality and its broader impacts on public health, the environment, and the economy. Recognising the critical importance of addressing the pressing issue of air pollution, this study delves into various facets of the MopFan technology and its potential for revolutionising the field of air purification. To lay the foundation for this research, a thorough review of the existing literature on photocatalytic purifiers is conducted, providing a comprehensive understanding of the current state-of-the-art in air purification technology. By analysing the strengths and limitations of previous studies, this review identifies crucial areas for improvement, particularly in the domains of filter design, catalyst selection, and lighting arrangement. By pinpointing these areas, the study aims to contribute to the ongoing efforts to enhance the efficacy and efficiency of air purification systems.